OPS Development of Authentic Assessment Instruments Based on Character Education in Elementary School - Manurung, Suprapto; Sijabat, Osco Parmonangan; Sidabutar, Ropinus; Hasibuan, Ronald (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2022)
This study aims to develop an authentic assessment instrument for spiritual attitudes and social attitudes based on character education in grade IV SD Negeri 125138 Pematangsiantar. The research method uses research and development (R & D) with a development model according to Borg and Gall. The development of the thematic average instrument based on character education and equipped with an authentic assessment instrument for spiritual attitudes and social attitudes based on character education has proven to be effective. The pretest learning outcomes of the control and experimental classes, namely the control class were 57.16 while the experimental class was 60.28. After the trial was carried out for 6 meetings, the average posttest score in the control and experimental groups increased to 71.36 and 75.56. The results of the t-test obtained tcount = 6.280 with a significance level of Sig. (2-tailed) 0.002 < = 0.05. The control class students' learning activities reached an average of 52% in the good enough category and the experimental class reached an average of 88.6% in the good category. Thus, the increase in student learning outcomes was higher in the experimental group. The N-Gain obtained is 0.54 which shows the number <0.6 which means that it is very effective.